Możliwość współczesnej profilaktyki szkolnej = The potential of contemporary school prevention - Kowalski, Mirosław; Radziwołek, Marcin (Zielona Góra: Lubuskie Towarzystwo Naukowe)
The school is a place where universal prevention is implemented, usually aimed at low-risk groups. School prevention is understood as all the activities protecting young people from developmental disturbances and adequate intervention measures in situations of emerging risks. Such prevention includes activities undertaken during the implementation of all teaching and upbringing programmes, when the general tasks of the school are carried out, including activities specific to prevention.
Keywords: school; prevention; education; students; youth; szkoła; profilaktyka; uczeń; edukacja; młodzież